Windows 8 Bible - Boyce, Jim, 1958- (John Wiley & Sons, 2013)
BThe first and last word on the feature-packed new Windows 8/b/ Windows 8 is an exciting new version of Microsoft's flagship operating system and it's packed with exciting new features. From the new Windows 82032s lock screen and the new Internet Explorer to a built-in PDF reader and new user interface, Windows 8 is not only a replacement for Windows 7 but a serious OS for today's tablet and touchscreen device users. And what better way to get the very most out of it than with this equally impressive new book from Microsoft experts' Over 900 pages packed with tips, instruction, and techniques help you hit the ground running with Windows 8./ ulliProvides complete how-to coverage of Windows 8 in a thoroughly redesigned and revised new Bible from an expert author team /liliCovers all the exciting new Windows 8 features, including the Windows 82032s lock screen, Internet Explorer Immersive, Modern Reader, a new interface, and more /liliHelps new and inexperienced users, as well as those upgrading from Windows 7, Windows Vista, or Windows XP /liliAlso explores new connections to cloud applications and data, distributed file system replication, and improvements to branch cache/li/ul Get the very most out of Windows 8, no matter what device you run it on, with iWindows 8 Bible./i.